2011
DOI: 10.1002/bip.21619
|View full text |Cite
|
Sign up to set email alerts
|

Brownian dynamics study of the association between the 70S ribosome and elongation factor G

Abstract: Protein synthesis on the ribosome involves a number of external protein factors that bind at its functional sites. One key factor is the elongation factor G (EF-G) that facilitates the translocation of transfer RNAs between their binding sites, as well as advancement of the messenger RNA by one codon. The details of the EF-G/ribosome diffusional encounter and EF-G association pathway still remain unanswered. Here, we applied Brownian dynamics methodology to study bimolecular association in the bacterial EF-G/7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 109 publications
0
17
0
Order By: Relevance
“… 987 BD has also been used to study association of elongation factor G with the ribosome. 986 These BD calculations demonstrate that diverse computational approaches can complement each other in studies on various aspects of the ribosome’s function.…”
Section: Simulations Of Specific Rna Systemsmentioning
confidence: 91%
See 1 more Smart Citation
“… 987 BD has also been used to study association of elongation factor G with the ribosome. 986 These BD calculations demonstrate that diverse computational approaches can complement each other in studies on various aspects of the ribosome’s function.…”
Section: Simulations Of Specific Rna Systemsmentioning
confidence: 91%
“…BD simulations were also used to study the kinetics and association of paromomycin to the entire 30S ribosomal subunit. 986 The resulting model suggested that specific binding at the ribosomal A-site starts with nonspecific antibiotic diffusion toward the 30S subunit and is followed by exploration of the subunit’s surface. 977 The calculations did not suggest any specific long-range electrostatic navigation through the landscape to the A-site, but identified two entrances to the A-site around which the mobility of paromomycin is high.…”
Section: Simulations Of Specific Rna Systemsmentioning
confidence: 99%
“…first provided evidence for electrostatic steering using Brownian dynamics. Subsequently a number of simulation studies have observed electrostatic steering during productive complex formation in protein–protein association. Aided by Brownian dynamics simulations, the kinetic mechanism of protein association is now a mature field.…”
Section: Introductionmentioning
confidence: 99%
“…This method so far cannot provide kinetic information of binding. On the other hand, Brownian dynamic simulation, and a more recently developed method based on transient‐complex theory give promising results on predicting kinetic rates of protein association. However, the extension of these methods to membrane protein association is currently under development.…”
Section: Introductionmentioning
confidence: 99%